2006
DOI: 10.1115/1.2735347
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Solar Cells by Application of a Polymer Coating Containing a Luminescent Dye

Abstract: One of the major loss mechanisms in state of the art photovoltaic cells is spectral loss resulting from inefficient use of ultraviolet photons and the lack of absorption of infrared photons by the solar cell. For a Si solar cell, e.g., spectral losses alone result in over 55% loss of the energy of the solar spectrum. Converting the spectrum of the incoming light such that it has a better match with the absorption spectrum of the solar cell can reduce spectral losses, especially in the case of a small absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Their wide applications in opto-electronic materials, 1-8 solar cells, [9][10][11][12][13] non-linear optics, [14][15][16][17] and sensors [18][19][20][21][22] as well as the challenge to understand the origin of emission have kept motivated the solid state photophysics community. The packing of aromatic organic chromophores strongly impacts their solid state fluorescence.…”
mentioning
confidence: 99%
“…Their wide applications in opto-electronic materials, 1-8 solar cells, [9][10][11][12][13] non-linear optics, [14][15][16][17] and sensors [18][19][20][21][22] as well as the challenge to understand the origin of emission have kept motivated the solid state photophysics community. The packing of aromatic organic chromophores strongly impacts their solid state fluorescence.…”
mentioning
confidence: 99%
“…For these purposes the chosen materials were indeed many, with the most frequent categories being polymers such as polymethyl methacrylate (PMMA) [7][8][9] or poly-vinyl acetate [10,11], and they can exhibit high transparency in the visible region of the spectrum, adequate resistance to heat and humidity variations, and high mechanical strength [12]. They also provide very good host environment for organic dye molecules [13].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of luminescent materials have been investigated for LDS and can be separated into three main categories: quantum dots (QDs) [14][15][16][17][18], organic dyes [7][8][9] and rare-earth ions/complexes [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the potential for efficiency and stability enhancements via LDS layers have been reported in a wide range of PV technologies, including Dye Sensitised Solar Cells (DSSCs) [9], there are only a limited number of studies that have been carried out on OPV materials [10] and devices [11,12,13]. In particular, Sloff et al and Engmann et al have reported promising results that show a photocurrent improvement by applying LDS layers in OPVs, but the stability issue was not addressed.…”
Section: Introductionmentioning
confidence: 99%